2008
DOI: 10.1530/eje-08-0197
|View full text |Cite
|
Sign up to set email alerts
|

Serum vascular endothelial growth factor levels in patients with medullary thyroid carcinoma

Abstract: Background: High levels of vascular endothelial growth factor (VEGF) have been reported in patients with cancers of different origins. There are no data comparing serum VEGF levels of medullary thyroid carcinoma (MTC) patients with that of the healthy subjects. Objective: We tried to assess whether serum VEGF concentration in MTC patients is correlated with tumour extension and whether this marker might be used to further refine the selection of candidates for future therapies with receptor tyrosine kinase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Of these patients, 22 had localized disease (TNM I-II) and 16 had metastatic disease (TNM III-IV), but the staining signal of VEGF-A did not differ between them. These findings are consistent with a recent study that did not observe a correlation between serum VEGF levels and the extent of disease in MTC patients (36).…”
Section: Vegf-a Expression In Medullary Thyroid Carcinoma 867supporting
confidence: 93%
“…Of these patients, 22 had localized disease (TNM I-II) and 16 had metastatic disease (TNM III-IV), but the staining signal of VEGF-A did not differ between them. These findings are consistent with a recent study that did not observe a correlation between serum VEGF levels and the extent of disease in MTC patients (36).…”
Section: Vegf-a Expression In Medullary Thyroid Carcinoma 867supporting
confidence: 93%
“…p53 mutants have been shown to bind poorly to DNA, thus repressing its tumor-suppressor activity. Regression analyses have linked TP53 genotype mutations to an inherited increase in the risk of sporadic MTC (Joao Bugalho et al, 2008; Barbieri, 2012). …”
Section: Genes Involved and Proteinsmentioning
confidence: 99%
“…They found that the levels of serum VEGF were remarkably higher in patients with distant metastases than those in remission or healthy patients, suggesting that it may be used as a marker of thyroid cancer with distant metastases. Bugallho, et al, however, found that serum concentration of VEGF in MTC patients were not significantly different from those found in healthy subjects and did not correlate with the extension of disease [169]. Narita, et al also reported a decreased VEGF-D serum levels in patients with metastases of differentiated thyroid cancer, regardless of the degree of metastatic spread [170].…”
Section: Vegf and Vegfrmentioning
confidence: 93%